On intra-urban differences in the destinations of emigrants from the Municipality of Malaga (Spain): An approximation based on the municipal register of inhabitants. - Batista-Zamora, Ana Ester; Larrubia-Vargas, Remedios; Natera-Rivas, Juan José (Geographical Institute, Research Centre for Astronomy and Earth Sciences (CSFK). Budapest, Hungría., 2024)
Emigrants who left the Municipality of Malaga in the 2017–2021 period went to multiple destinations, mostly municipalities located in the province of Malaga itself, more specifically in its metropolitan area. Average housing prices in these metropolitan municipalities are highly variable, and, in this context, it is reasonable to assume that there will be a relationship between the income levels of emigrants and their destination. Based on a special processing of the Municipal Register of Inhabitants of the Municipality of Malaga, we show how a relationship can effectively be found between the average household income (AHI) of the census tract of origin of the emigrants and the average price of housing in the destination municipality, both for the whole group of emigrants and for selected age groups – children and young adults. A relationship that points to an overrepresentation of municipalities with high housing prices in the sections with the highest income, and vice versa.
Keywords: Migración interna - Málaga (Provincia); Municipality of Malaga; Residential migration; Municipal register of inhabitants; Average household income